2017
DOI: 10.1007/978-3-319-63260-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Implications of Obesity in Neuroinflammation

Abstract: Since the discovery of the remarkable properties of adipose tissue as a metabolically active organ, several evidences on the possible link between obesity and the pathogenesis of multiple sclerosis (MS) have been gathered. Obesity in early life, mainly during adolescence, has been proposed as a relevant risk factor for late MS development. Moreover, once MS is initiated, obesity can contribute to increase disease severity by negatively influencing disease progress. Despite the fact that clinical data are not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Several studies have repeatedly shown that obesity is a risk factor for early-onset MS 3537 . While the underlying mechanism by which obesity contributes to MS etiology remains unclear several hypotheses have been postulated including; the effect of persistent low-grade neuroinflammation 38 , the role of adipose tissue adipokines in promoting inflammation 39 , and obesity-related central nervous system cardiovascular alterations 40 . The role of obesity in MS expands beyond risk as it has been shown to worsen MS disease disability and progression as well 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have repeatedly shown that obesity is a risk factor for early-onset MS 3537 . While the underlying mechanism by which obesity contributes to MS etiology remains unclear several hypotheses have been postulated including; the effect of persistent low-grade neuroinflammation 38 , the role of adipose tissue adipokines in promoting inflammation 39 , and obesity-related central nervous system cardiovascular alterations 40 . The role of obesity in MS expands beyond risk as it has been shown to worsen MS disease disability and progression as well 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, especially in adolescence has been reported to have an effect on MS susceptibility, but it is unclear whether this may be attributed to genetically determined factors or environmental/ socio-economical influences or a combination of different effects, e.g., a low-grade neuro-inflammatory effect or a vitDsequestering effect (50)(51)(52)(53).…”
Section: Ms Etiology and Epidemiologymentioning
confidence: 99%
“…This issue is of highest relevance given that, so far, modification of vascular risk factors has shown only limited effects to slow the progression of WMH. 20 Systemic inflammation has also been suggested to affect white matter, 21 and circulating cytokines were related to increased WMH volume in several large cohorts. Particularly, the distinction between patchy WMH around the ventricles (periventricular, pvWMH) versus more confluent WMH in the deep white matter (dWMH) may be of relevance.…”
mentioning
confidence: 99%
“…Notably, obesity and visceral fat especially contribute to systemic low‐grade inflammation through release of cytokines such as interleukin‐6 (IL6) and C‐reactive protein (CRP) . Systemic inflammation has also been suggested to affect white matter, and circulating cytokines were related to increased WMH volume in several large cohorts . Thus, low‐grade inflammation could be an independent mechanism of obesity‐related white matter damage.…”
mentioning
confidence: 99%